2021
DOI: 10.3390/agronomy11081598
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Nutrient Uptake, Photosynthesis and Yield of Tomato to Biochar Addition under Reduced Nitrogen Application

Abstract: Tomato is an important economic crop that is widely consumed worldwide. Tomato production is mainly limited by the use of nitrogen fertilizer, sunlight, soil and water conditions. Biochar is one of the soil amendments, and it is recognized as a promising practice for improving crop production in agriculture. The effect of biochar on the photosynthetic traits and tomato yield under reduced nitrogen fertilizer application is still not well understood. The objective of this research is to investigate the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The synergistic or complementary interaction between BC and N improves soil nutrient availability and enhances slow-release performance of fertilizer ( Chen et al., 2018 ). These findings are consistent with previous studies conducted by Guo et al. (2021) and Omara et al.…”
Section: Discussionsupporting
confidence: 94%
“…The synergistic or complementary interaction between BC and N improves soil nutrient availability and enhances slow-release performance of fertilizer ( Chen et al., 2018 ). These findings are consistent with previous studies conducted by Guo et al. (2021) and Omara et al.…”
Section: Discussionsupporting
confidence: 94%
“…The promotion of fruit quantity and quality could be attributable to the high total P content in the biochar-treated substrate and the high total N concentration in roots of the biochar-treated plants observed at high level. Indeed, according to other reports, there might be a relationship between the phosphorous and nitrogen contents in both growing substrates and plant tissues and the promotion of fruit production by improving the vegetative and reproductive properties of tomato plants (Hameeda et al, 2019), also attributed to the increased values of lycopene, titratable acidity, and total soluble solids when biochar was used as a soil amendment (Guo et al, 2021). The continuous application of 20 t ha −1 of rice biochar to a rice field resulted in plant growth promotion and an increase of 14%-26% in soil N uptake, 7%-11% in internal N use efficiency, and a 6% in grain yield (Gomez et al, 2022).…”
Section: Effects On Crop Yield/productivitymentioning
confidence: 93%
“…One study found that the biochar application significantly increased plant uptake of nitrogen and phosphorus and improved leaf photosynthetic characteristics. 42 Moreover, our research revealed that BCAF could enhance the absorption and transformation of light energy. The photosynthetic performance index (PI ABS and PI Total ), driving force (DF ABS and DF Total ), potential photochemical efficiency (F v /F 0 ), and quantum yield (φ E0 ) for electron transfer in the high biochar dose Note: Different letters in different treatments indicated significant difference (P < 0.05), while the same letter indicated no significant difference (P < 0.05).…”
Section: Effects Of Long-term Co-application Of Biochar and Fertilize...mentioning
confidence: 73%
“…The promoting effect of biochar on soil phosphorus also provides favorable conditions for improving crop photosynthetic capacity. One study found that the biochar application significantly increased plant uptake of nitrogen and phosphorus and improved leaf photosynthetic characteristics 42 …”
Section: Discussionmentioning
confidence: 99%